Lactic Acid Fermentation Exposed to Some Alkaloids - Singh, S.P.; Kumar Pandey, Shanti; Chaurasia, P.K.; Brahamchari, A.K.; Pratap, Birendra; Yadvan, L.D.P. (Asian Journal of Chemistry, 2010)
The influence of brucine, berberine, hypaphorine and morphine on production of lactic acid by L. delbrueckii has been studied. It has been found that berberine has an inhibitory effect on lactic acid fermentation while brucine, hypaphorine and morphine stimulates the fermentation process.